Implementasi Firebase Realtime Database pada Aplikasi FeedbackMe sebagai Penghubung Guru dan Orang Tua - Khairun Nisa Meiah Ngafidin; Artika Arista; Rona Nisa Sofia Amriza (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
The necessity of learning assistance for elementary student is to ensure that students can absorb the learning well. In order to keep track of the student's progress, the teacher needs to know how and what the student has done while at home. The FeedbackMe application was created to become a liaison between teachers and parents during distance learning. Firebase Realtime Database is implemented to support messages to be delivered quickly. The purpose of this study is to implement the Firebase Realtime Database into the FeedbackMe application to support remote student learning. The system development method used is the Waterfall method which is a systematic and sequential method. The results of this study indicate that all the features in the application and also the application of Firebase can run properly and correctly. Meanwhile, testing of respondents regarding user satisfaction results in the amount of 89.28% from teacher, and respondents from parents got 89.73% satisfaction.